Enhanced peroxidase activity and tumour tissue visualization by cobalt-doped magnetoferritin nanoparticles. (16th December 2016) - Zhang, Tongwei; Cao, Changqian; Tang, Xu; Cai, Yao; Yang, Caiyun; Pan, Yongxin
Abstract: Magnetoferritin (M-HFn) is a biomimetic magnetic nanoparticle with a human heavy-chain ferritin (HFn) shell, trapping a magnetite (Fe3 O4 ) core that has inherited peroxidase-like activity. In this study, cobalt-doped M-HFn nanoparticles (M-HFn-Co x Fe3– x O4 ) with different amounts of cobalt were successfully synthesized. Experimental results indicate that the controlled doping of a certain amount of cobalt into the magnetite cores of M-HFn nanoparticles enhances its peroxidase-like catalytic activity and efficacy for visualizing tumour tissues. For example, compared with sample Co0 (without cobalt doping), the peroxidase-like activity of the cobalt-doped nanoparticle sample Co60 (with a cobalt doping molar percentage of ∼34.2%) increases 1.7 times, and has the maximal reaction velocity ( V max ) values. Moreover, after a one-step incubation with Co60 nanoparticles, and using the peroxidase substrate 3, 3′-diaminobenzidine tetrahydrochloride (DAB) for colour development, the tumour tissues of breast, colorectal, stomach and pancreas tumours showed a deeper brown colour with clear boundaries between the healthy and tumourous cells. Therefore, this suggests that the cobalt-doped magnetoferritin nanoparticles enhance peroxidase activity and tumour tissue visualization.